Congenital Pyloric Atresia with Distal Duodenal Atresia- Role of CT Scan - Yogender Singh Kadian; KN Rattan (EL-Med-Pub, 2014)
The mainstay of diagnosis of congenital pyloric atresia is by plain X-ray of the abdomen showing a large gas bubble with no gas distally. But very rarely it can be associated with distal duodenal atresia when the baby may present as lump abdomen. In such a situation apart from the X-ray, another radiological investigation is needed to delineate the exact nature of the lump. Since the role of ultrasonography is limited in intestinal pathologies and contrast studies are not informative in atresias, the CT scan is the ideal choice. We had managed a case of pyloric atresia with similar presentation with preoperative CT scan.